Pleistocene volcanism and the geomorphological record of the Hrazdan valley, central Armenia: linking landscape dynamics and the Palaeolithic record. (15th December 2019) - Sherriff, J.E.; Wilkinson, K.N.; Adler, D.S.; Arakelyan, D.; Beverly, E.J.; Blockley, S.P.E.; Gasparyan, B.; Mark, D.F.; Meliksetian, K.; Nahapetyan, S.; Preece, K.J.; Timms, R.G.O.
Abstract: The Southern Caucasus lies at the intersection of Africa, the Levant and Eurasia, and is thus a region of considerable interest in the study of Pleistocene hominin population dynamics and behaviour. While Palaeolithic archaeological sites in the region such as Dmanisi and Nor Geghi 1 attest to such palaeogeographic significance, a greater understanding of the chronology and nature of climatic and geomorphic changes in the region is needed to fully understand hominin settlement dynamics. The Hrazdan river valley, central Armenia, has the potential to offer such insights given its rich Palaeolithic record and complex history of Pleistocene infill as a result of alluvial, lacustrine, aeolian, and volcanic processes. We therefore present a stratigraphic framework for basin infill and hominin activity during the Pleistocene, based on extensive geomorphological and geological mapping, published chronometric results ( 40 Ar/ 39 Ar and K-Ar), and archaeological survey. We demonstrate that the onset of Pleistocene volcanism in the Gegham Range to the immediate east of the Hrazdan valley occurred around 700 ka BP, after which there were several phases of effusive eruption lasting until 200 ka. Interbedded with lava emplaced by these eruptions are alluvial and lacustrine sequences, some with evidence of pedogenesis and several of which have yielded Palaeolithic artefacts. Taken together these sequences suggest a cyclical model of infill whereby lava flow along the valley resulted in the blockage of the palaeo-Hrazdan river and lake formation in the lea of the lava dams. Breaching of these dams resulted in a shift to predominately fluvial deposition, and the consequent development of floodplain soils. Hominin populations exploited the floodplains at times when the last of these phases coincided with interglacial and interstadial climates, but they also occupied the surrounding valley sides during the same warm, humid phases. Highlights: Development of a stratigraphic framework for volcanism, landscape development and Palaeolithic occupation in the Central Armenian Highlands. Demonstrates several phases of effusive and explosive volcanic activity during the Middle and Late Pleistocene. Landscape change was caused by a combination of volcanic activity, hydrological development and climate change. Preservation of stratified Palaeolithic sequences indicates that hominins were exploiting floodplain and lake environments during warm episodes. Close association of sedimentarysequences and volcanic products provides a rare opportunity for precisely dating Palaeolithic occupations.